Feminizing the habit of reading - Gema Lasarte (Ocnos, 2013)
This article presents the results of a descriptive research on the feminization of reading field in the Basque Literature for young readers. This research maintained the thesis that the progressive increase in women’s presence in the Basque literary system would have also to be projected somehow in the reading field. The questionnaire was used as a methodological tool and a school children population of boys and girls aged between 11-12 years was chosen in Vitoria. The preliminary hypothesis was verified, though a clear trend of female presence in girls readings than in boys ones has been detected. Women read an imaginary world 21.6. % more feminine than men do.